1985
DOI: 10.1021/jf00063a005
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds from Penicillium sp. contributing musty-earthy notes to Brie and Camembert cheese flavors

Abstract: Volatile headspace compounds collected on Tenax GC at room temperature (21 °C) from pure cultures of Penicillium caseicolum and Penicillium camemberti grown on potato dextrose and Czapek's agar were separated by gas chromatography and identified by mass spectrometry, retention indices (/E), and odor quality. P. camemberti and P. caseicolum produced similar volatile compound profiles. Mushroom-like, green plant-like aromas were contributed by l-octen-3-ol, l,5-octadien-3-ol, l,5-octadien-3-one, 3-octanol, and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(64 citation statements)
references
References 30 publications
1
61
0
2
Order By: Relevance
“…Various esters have been detected in every soft cheese studied (Table 4). For example, 57 esters have been identified by Gallois and Langlois (1990) in Dumont et al, 1974a;(25) Dumont et al, 1974b;(26) Dumont et al, 1974c;(27) Dumont et al 1976a;(28) Dumont et al, 1976b;(29) Dunn and Lindsay, 1985;(30) Gallois and Langlois, 1990;(31) Groux and Moinas, 1974;(32) Hall and Anderson, 1983;(33) Hardi, 1987; (34) Karahadian et al, 1985a;(35) Laing et al, 1978;(36) Moinas et al, 1973;(37) Roger et al, 1988. Blue cheeses where they constitute 6-15% of the aroma compounds.…”
Section: Neutral Compoundsmentioning
confidence: 99%
“…Various esters have been detected in every soft cheese studied (Table 4). For example, 57 esters have been identified by Gallois and Langlois (1990) in Dumont et al, 1974a;(25) Dumont et al, 1974b;(26) Dumont et al, 1974c;(27) Dumont et al 1976a;(28) Dumont et al, 1976b;(29) Dunn and Lindsay, 1985;(30) Gallois and Langlois, 1990;(31) Groux and Moinas, 1974;(32) Hall and Anderson, 1983;(33) Hardi, 1987; (34) Karahadian et al, 1985a;(35) Laing et al, 1978;(36) Moinas et al, 1973;(37) Roger et al, 1988. Blue cheeses where they constitute 6-15% of the aroma compounds.…”
Section: Neutral Compoundsmentioning
confidence: 99%
“…Dimethyl disulphide and the other sulphur compound dimethyl trisulphide (important on PC2) result from the degradation of sulphur containing amino acids. These two sulphur compounds have been reported in aged Brie and Swiss cheeses [23,46], Parmesan cheese [6], Fontina cheese [4] and a number of hard type cheeses [11]. Mariaca et al [31] investigated the terpenoid content of forty-seven plants from lowland and highland pastures from which cheeses were made.…”
Section: Volatile Compositionmentioning
confidence: 99%
“…The author identified geosmin, MIB and 2-methoxy-3-isopropyl pyrazine (MiPP) as responsible for mouldy/earthy odours. Karahadian et al [10] showed that Penicillium type moulds used in camembert manufacture could generate mouldy/earthy notes. Oxygenated derivatives of octane, MIB, and MiPP were identified.…”
Section: Introductionmentioning
confidence: 99%